Immunological Responses of Marine Bivalves to Contaminant Exposure: Contribution of the -Omics Approach - Balbi, Teresa; Auguste, Manon; Ciacci, Caterina; Canesi, Laura (Frontiers in Immunology, 2021)
The increasing number of studies on the biological impact of anthropogenic chemicals in the marine environment, together with the great development of invertebrate immunology, identified marine bivalves as a key invertebrate group for studies on immunological responses topollutant exposure. Available data on the effects of contaminants on bivalve immunity, evaluated with different functional and molecular endpoints, underline that individual functional parameters (cellular or humoral) and expression of selected immune related genes can distinctly react to different chemicals depending on the conditions of exposure. Therefore, measurement of a suite of immune biomarkers in hemocytes and hemolymph is needed for the correct evaluation of the overall impact of contaminant exposure on the organism immunocompetence. Recent advances in –omics technologies are revealing the complexity of the molecular players involved in the immune response of different bivalve species. Although different –omics represent extremely powerful tools in understanding the impact of pollutants on a key physiological function such as immune defense, only in the last few years the –omics approach has been utilized in this area of investigation. In this work, available information obtained from the application of –omics to investigate the effects of pollutants on bivalve immune responses is summarized. From these data it emerges that the overall knowledge on this subject is still quite limited and that, in order to understand the true environmental significance of any immune dysfunction caused by exposure to contaminants , a combination of both functional assays and cutting-edge technology (transcriptomics, proteomics, metabolomics) is required. In addition, the utilization of metagenomics may explain how the complex interplay between the immune system of bivalves and its associated bacterial communities can be modulated by pollutants, and how this may in turn affect homeostatic processes of the host, host-pathogen interactions and increased susceptibility to disease. Integrating different approaches will contribute to better define the mechanisms underlying the immune response to pollutants in ecologically and economically relevant bivalve species and to explain their sensitivity to multiple stressors, thus resulting in health or disease.